P. 1
Unit 5

# Unit 5

|Views: 199|Likes:

See more
See less

04/05/2013

pdf

text

original

# UNIT 5

DERIVATIVES OF SOME STANDARD FUNCTIONS

Structure
Introduction
Objectives

Exponential Functions
5.2.1 Definition o f an Exponential Function 5.2.2 Derivative of an Exponential Function

Derivatives of Logarithmic Functions
5.3.1 Differentiating the Natural Log Function 5.3.2 Differentiating the General Log Function

Hyperbolic Functionls
5.4.1 Definitions and Basic Properties 5.4.2 Derivatives of Hyperbolic Functions 5.4.3 Derivatives of Inverse Hyperbolic Functions

Methods of Differentiation
5 5.1 5.5.2 5.5.3 5.5.4 Derivative of xr Logarithmic Differentiation Derivatives o f Functions Defined in Terms o f a Parameter Derivatives of Implicit Functions

s m ay u mr

5.1 INTRODUCTION
Exponential functions occupy an important place in pure and applied science. Laws of growth and decay are very often expressed in terms of these functions. In this unit we shall study the derivatives of exponential functions. The inverse function theorem which was stated in Unit 4 will then help us to differentiate this inverse, the logarithmic functions. In particular, you will find that the natural exponential function in its own derivative. Further we shall introduce and differentiate hyperbolic functions and their inverses since they hold special significance for physical sciences. We shall demonstrate the method of finding derivatives by taking logarithms, and also that of drfferentiating implicit functions. With this unit we come to the end of our quest for the derivatives of some standard, frequently used functions. In the next block we shall see the geometrical significance of derivatives and shall use them for sketching graphs of functions.

Objectives
After studying this unit you should be able to : find the derivatives of exponential and logarithmic functions define hyperbolic functions and discuss the existence of their inverses differentiate hyperbolic functions and inverse hyperbolic functions use the method of logarithmic differentiation for solving some problems differentiate implicit functions and also those functions which are defined with the help of a parameter.

5.2 EXPONENTIAL FUNCTIONS
Our main aim, here, is to find the derivatives of exponential functions. But let us first recall the definition of an exponential function.

5.2.1

Definition of an Exponential Function
d

Derivatives of Some Standard Functions

A function f defined on R by f(x) = ax, where a > 0, is known as an exponential function. Now to find the derivative of i we shall have to take the limit: :

h-+O

lim

ax+b

-

ax

h if we put

= a x . lim h-,O

ah - I h

a" may not be defined for all

...

x if a<O. For example, (-2)"'
i s not defined In

H.

SO,

: !A

- k, we get -

ah - I
h

k

=

a' = k . a'. We can also Interpret k as the derivative of a" at x dx see the graphs of exponential functions for various values of a.
-

cl -

-

h a - I lim h-to h

0. In Fig. 1 you can

A Y

=

- (a")
dx

d

I

I

-- 0

Fig. 1

All these curves pass through (0, 1) as a0 = 1 for all a. Now from all these curves, we shall choose that one, whose tangent at (0, 1) has slope = 1. (We assume that such a curve exists). The value of a corresponding to this curve is then denoted by e. Thus, we have singled out the exponential function : x + ex, so that its derivative at x = 0 is 1. Thus, e h -1 lim --- 1 h->O h This also means that dex - ex el'-~ - lim . e x .lim -= e dx h->O h h+O .h That is, the derivative of thls function is the funct~on itself. Thls special exponential function IS called the natural exponential function.
- -

-

5.2.2 Derivative of an Exponential Function
In Unit 1, we compared the graphs of natural exponential function ex and the natural logarithmic function Inx and found that they are reflections of each other w.r.t. the line y = x (see Fig. 2). We concluded that ex and lnx are inverses of each other. This also means that el"" x y x > 0.

-

-

big. ?

Elements o f Differential CnIcuIus

F om this we can write

C

ax = elna' , or ax = exlna,where a > 0.

h a b = blna
I

ex In a

dx = e x In a I n a = ax In a.

d -(x In a) by chain rule

Remark 1 If we compare this result with (1) which we derived at the beginning of this section, we find that ah - 1 In a = lim h Thus, we have

,

d - ex = ex, and
dx

Example 1 Let us use these formula to find the derivatives of

ii)

ex -+ e-X ex -e-X

.

ill)

asin-' r

9

Let y

-

,

. Then, by chain rule

-

(ex -e-') (ex - -- - (e' +e-') (r' -+- - X ) e-X) ---.e(e\ - e-' ) =

i Ws )

dpp

'he chain rule again to different~atc,"" " x

bc.

vou can solve these exercises now the derivatives of :

E

E

1,

I- ur

Derivatives of Some Standard Functions

E 2) How much faster is f(x) = 2x increasing at x

=

112 than at x

=

O?

E

lim In this section we have defined e as that real number for which h+o Alternatively, e can also be defined as a limit: e
= h+O

h

h

=

1.

lim (1 + lin)", or as the sum of an infinite series: e

=

1 1 1 + - + - + .... l! 2!

But all these definitions give the same value, e = 2.718281828 ... e is an irrational number. In many situations the rate of growth (of human beings, or bacteria or radioactive particles) is proportional to the present population. That is, if x(t) is the population at dx time t, then -.c x. In such situations the exponential function is of great relevance dt d since - (e') = et dt Now let us turn our attention to logarithmic functions.

1

5.3

DERIVATIVES OF LOGARITHMIC FUNCTIONS

In Unit 4, we studied the inverse function theorem, (Theorem 1, Unit 4) and used it to find the derivatives of various functions such as sin-'x, cos-'x, and so on. Here, we shall, yet again, apply this theorem to calculate the derivative of the natural logarithmic function.

5.3.1 Differentiating the Natural Log Function
Consider the function y = lnx. This is the inverse of the natural exponential function, that is, y = lnx if and only if x = eY. From Fig. 2, you can see that the natural exponential function is a strictly increasing function. (You will be able to rigorously prove this result by the end of this course). Further, the derivative of the function x = eYis
Inx is defined on 1 -[ 0

Elements o f Differential Calculus

d) d = - (ey) = e' , for all y E R. 0 dx dx Thus, all the conditions of the inverse function theorem are satisfied. This means we can conclude that the derivative of the natural logarithmic function (which is the inverse of the natural exponential function) exists, and dy dx
-

dx

d (Inx)

= ---- -

1

dxldy

- -- 1 - 1

e Y

x

Thus, we have

Let's see how we can use this result. Example 2: Suppose we want to differentiate y
=

In (x"

2x + 2).

Note that x2 - 2x

+

2 = (x - I ) + 1 and hence, is non-zero for all x. ~

Therefore, ln(x2- 2x + 2) is well-defined.

Example 3: If we want to differentiate y

=

In

I 1,

1 + x2 j ; I x I t 1. we will have to -i

consider two cases: i) I x I > 1 and ii) ( x ( < 1

since ( x I > 1 makes 1 - x2 negative. So in this rase.

-

4x I-x

4

, after simplification.

ii)

whe111 x 1 < 1,

1-1

1 + x2
=

1 + x2

and so.

a' i s a constant function for a = I Hence, 11 does not have any lnverse The log functions are thus defined a-Qtra+ I

4x 1- x
4
--

dy 4x = - - for all x such that 1 x 1 # l - 4 dx I - u Now, let us turn our attention to logarithmic funct~ons with
So. wc see that

n1171trat y

bases

5.3.2

Differentiating the General Log Function

Let us consider any positive number a # 1. We say logax = y if and only if x fi~nction can be written as logex. Inx Obviously. the natural logarithm~c

-

a'

Further, we know that logax = loc~,c Inx This rule gives a connection between the natural function, ' v c <hall usc thls relat~onshipto find the derivative of and general Iogar~thm~c loga x
So if v
=

logax = logae lnx.

d dx If we put a

-(log, x ) = log,e

1 x = 3 in this, we get our earlier result:

.-

Derivatives of Some Standard Functions

dy d lnx dx dx Thus, we arrive at d dx If we put a
-

- = log,e - = log,e -

1 x

-(log, x) = log, e =

x e in this, we get our earlier result:

.1

1 d lnx = - , since logee = 1 dx x

Example 4 Let us differentiate y = log,tan3x
- = log, e

dy dx

I d 3 - (tan x) tan3 x dx 1 = log, e tan3 x 3 tan2 x sec2 x sec2 x = 3 log, e tan x
-

If you have followed the solved examples in this section you should have no difficulty in solving these exercises.

E E 3) Find the derivatives of :
a) log, 2x
b) 71oglI (5x2 + 2)

c) e-"lnx

Elements o f Differentlal Calculus

5.4

HYPERBOLIC FUNCTIONS

In applications of mathematics to other sciences, we, very often, come across certain combinations of eXand e-'. Because of their importance, these combinations are given special names, like the hyperbolic sine, the hyperbolic cosine etc. These names suggest that they have some similarity with the trigonometric functions. Let's look at their precise definitions and try to understand the points of similarity and dissimilarity between the hyperbolic and the trigonometric functions.

5.4.1

Defitlitions and Basic Properties
=

Definition 1 The hyperbolic sine function is defined by sinh x

ex + e-' 2

for all x E R.

The range of this function is also R.
Definition 2 The hyperbolic cosine function is defined by cosh x

- e-X
=

2

for all x E

R. The range of this function is [ I ,
You will notice that
+

-1.

sinh

(-x)

=

-

e-(-~)
=

+ e-X

=-

2 sinh (x), and 2

2
- e-X

cosh

(-x)=

- e-(-~) -

-

2

=

cosh x

In other words, the hyperbolic sine is an odd function, while the hyperbolic cosine is an even function. Fig. 3(a) and (b) show the graphs of these two functions.

Fig. 3 : Graph of (a) sinh x (b) cosh x

We also define four other hyperbolic functions as - e-(-~) e x - e-X4 tanh x = e-X , coth x = ex + e-' '
+

C

-

sech x

=

ex
t

+

e-x , cosech x

=

e x - ,-x

.

E

E 4) Verify that

a) cosh2x - sinh2x = 1 sinh x b) tanh x = c) 1 - taih2 x = sech2 x.

Derivatives o f Somr S t a n d a r d Functions

E E 5) Derive an identity connecting coth x and cosech x.

You must have noticed that the ider~titiesinvolving these hyperbolic functions are similar to those invo!ving trigonometric functions. It is possible to extend this analogy and get some more fc.~nulas.

* cosh x sinh x cosh (x h y) = cosh x cosh y * sinh x sinh y tanh x + tanh y
sinh (X h y)
=

sinh x cosh y

tanh (x

y)

=

1 k tanh x tanh y

Since we have seen that cosh2t - sinh2 t = 1, it is obvious that a point with coordinates (cosh t, sinh t) lies on the unit hyperbola: x2 - y2 = 1. (Hence the name, hyperbolic functions). We have a similar situation in the case of trigonometric functions. The point (cost, sint) lies on the unit circle: x2 + y2 = 1. That is why trigonometric fbnctions are also called circular functions. There is one major point of difference between the hyperbolic and circular functions, though. While t in sint, cost, etc. is the measure of an angle, the t which appears in sinht, cosht, etc. cannot be interpreted as the measure of an angle. However, it is sometimes called the hypberbolic radian.

I

5.4.2 Derivatives of Hyperbolic Functions
L

Since the hyperbolic functions are defined in terms of the natural exponential function, whose derivative we already know, it is very easy to calculate their derivatives, For example,

Elements of Differential Calculus

- e-X
sinh x
d dx
=

2
= -

. This means,
+

- (sinh x)

d (ex ;e-') dx

e-"

2

= cosh

x

Similarly, cosh x =

ex + e-" gives us 2
2
=

- (cosh x) =

d dx

- e-X

=

sinh x

In the case of tanh x
d dx

(ex - e-") (ex + e-') , we get (ex + e-X)2

- (tanh x) =

(ex + e-') (ex + e-') - (ex - e-') (ex - e-')

=

1 - tanh2 x

=

sech2 x

We can adopt the same method for finding the derivatives of coth x, sech x and cosech x. In Table 1 we have collected all these results.
Table 1

Function sinh x cosh x tanh x coth x sech x cosech x

Derivative cosh x sinh x sech2 x - cosech2x - sech x tanh x - cosech x coth x
=

Example 5: Suppose we want to find dyldx when y

tanh (1 - x2)

See if you can solve these exercises on your own.

E

E 6) Fhd f(x) when f(x) =
i ~ )

tanh

4x

+1
5

#

-

b) sinh e2"

C)coth (llx)

d) sech (ln x)

e) ex cosh x

Derivatives of Some Standard Functions

5.4.3 Derivatives of Inverse Hyperbolic Functions
We shall try to find the derivatives of the inverse hyperbolic functions now. Let us start with the inverse hyperbolic sine functions. From Fig. 3(a) you can see that the hyperbolic sine is a strictly increasing function. This means that its inverse exists, and

We have used the formula

for finding the roots of a quadratic equation here. Note that if eY
x -

- m,

Thus sinh-'x sinh-lx. Now,

=

In (x + J1 + x2 ), x E ] - m,

m

[. In Fig. 4, we have drawn the graph of

then eY < 0, which is impossible. Therefore we ignore this root.

d Thus, - (sirh-' x) dx

=. i

--

1

1 , I =
Again we ignore the root eY = x -

In the case of the hyperbolic cosine function, we see from Fig. 3 (b), that its inverse will exist if we restrict its domain to [0, -[. The domain of this inverse function will be [ l , w[, and its range will be [0, w[. Now y = cosh-' x

f i , because

then eY < I , which is impossible since y > 0.

o x

= cosh

y=

ey

+ e-y

,

Elements of Differential

Calculus

~ h u cash-' x s

-

~n (x *

\ I / ), x 2 1.
=

Fig. 5 shows the graph of cosh-'x. d Further - (cosh-' x)
dx

1 ----x+1

--

d dx ( x +

,,LEI

Note that the derivative of cosh-' x does not exist at x

=

1.

Fig. 6 (a), (b) and (c) show the graphs of tanh x, coth x and cosech x. You can see that each of these functions is one-one and strictly monotonic. Thus, we can talk about the inverse in each case. Arguing as for sinh-' and cosh-'x, we get

(b)
Fig. 6

y = cosech-'x

-

x
1

=

cosechy w y = in

[i '

,x#O
I

Since sech x =

-' we shall have to restrict the domain of sech x to [0, m[ before cosh x
E

talking about its inverse, as we did for coshx. ~ech--'x defined for all x is can write sech-' x = In [ l + ( y ) , O < x s l

10, I], and we

Now, we can find the derivatives of each of these inverse hyperbolic functions. We proceed exactly as we did for the inverse hyperbolic sine and cosine funcitons and get

L.erivntives o f Some Standard Functions

Let us use these results to solve some problems now.

I
I

Example 6 Suppose we want to find the derivatives of (a) f(x) = sinh-'(tanx), and (b) g(x) tad-'(cos ex).

-

f (x)

=

-1

d
-

J G dx
sec' x
=

(tan x).

-- 1 - Iec
Now if g(x)
=

1 sec x 1

tad-' (cos ex), this means that

- - -ex

sin e x

=-

ex cosec ex

We are now listing some functions for you to differentiate.

E

E7) Differentiate the following functions on their respective domains.
a) cosech-' (5 & ) C) coth-l e ( ~+5x-6) 2 e) sinh-' b) [sech-' (cos2 x)]"~

d) t a d - ' (coth x) + coth-' (2x)
(2x2)

& + cosh-'

Elements o f Differentlrl Calculus

5.5

METHODS OF DIFFERENTIATION

In this section, we shall study different methods of finding derivatives. We shall also see that the problem of differentiating some functions is greatly simplified by using these methods. Some of the results we derived in the earlier sections will be useful to us here.

5.5.1

Derivative of X '

In Unit 4 we have seen that
AS we have mentioned in Unit 4, if x < 0, xr may not be a

-(xr ) = rxr-' dx --

d

when r is a rational number. Now, we are in a
=

real number. For example, -3%-

position to extend this result to the case when r is any rea1,number. So if y x > 0 and r E R, we can write this as
= eln x r

xr, where

, m

E

R

, Inx , since the natural exponential and logarithmic functions are inverses of ,r

each other.

- re'.'"x This proves that d - (xr1 =
dx

1 - - rxr - r-',
X
X

l

for x > 0,

r E R.

We are surd, you will be able to solve this exercise now.

E

E 8) Differentiate a) x~

b) xe

5.5.2 Logarithmic Differentiation
Sometimes we find that the process of taking derivatives becomes simple if we take logarithms before differentiating. In this section we shall illustrate this point through some examples. But to take the logarithm of any quantity we have to be sure that it is nonnegative. To overcome this difficulty, let us first try to fmd the derivative of In ( I x I ). Now you can check easily that 1 x I =

Derivatives o f Some Standard Functions

0.

Therefore, I ( 1 x 1 ) = ln n

G ,and

We get,

d Using chain rule we can now conclude that if u is any function of x, then -In
dx

(1

u

1)

1 du -- -

u ' dx Let us see how this result helps us in simplifying the differentiation of some functions.
( x + 119 (X ~
(X

Example 7 To differentiate

- 31314 + 1)-113

- 5)213 (

x + 2~ ~

+ 1)-113

we start by taking y =

( x + 1)9 (X ~
(X

- 31314

- 51213(

x + 2~ ~

Then taking logarithms of both sides, we get

Differentiating throughout we get, 9 3 1 dy --

2x

ydx

x2+1

2 x + ----- - - - + 2 + 24(x - 3) 3(x - 5) 3(x2 + 2x + 1)

~ x a m ~8 Suppose we want to differentiate x""', x > 0. le

Let us write y = x ~ ' ' ' ~ . Then y > 0 and so we can take logarithms of both sides to the base e and write Iny
=

lnx""" = sin x.ln x

Differentiating throughout, we get.

sin - - x + cos x In x

Elements of Differential
CSICUIUS

heref fore

3 dx

=y

sin x' (T cosx lnx +

Example 9 Ta differentiate xCoSX(cosx)' let f(x) = xCoSX g(x) = cosxX.To ersure that + and f(x) and g(x) are well defined, let us restrict their domain to [0, ~ 1 2 1 .

y =x

cosx

+ ( c o ~ x =~ + g(x) ) f(x)

0 for x E

[o, ~ / 2 ]

,

Let us differentiate both f(x) and g(x) by taking logarithms. We have, f(x) = xW" Therefore lnf(x) = cosx lnx. Thus, 1 - f (x) f(x)
= - sin

1 x lnx + casx X

_

xcmx

(- sin x In x + cos x
X

- X~~~ - I (cos x - sin x In x)
= (cos x)'

Similarly, g(x)
I

and so Ing(x) = x ln cos x

g' (x) = In cos x

+ - (- sin x)
COS X

X

cos x In cos x - x sin x

-- (COSX)' (cosx In cosx - x sin x) dy Hence, - = f (x) + g' (x) dx
- xcow - 1 (cosx - xsinx lnx) + cosxX (cosx lncosx - xsinx) -

'

If you have followed these examples you should have no difficulty in solving these exercises by the same method.

E

E 9) Differentiate.

Derivatives o f Some Standard Functions

5.5.3 Derivatives of Functions Defined in Terms of a Parameter
Till now we were concerned with functions which were expressed as y = f(x). We called x an independent variable, and y, a dependent one. But sometimes the relationship between two variables x and y may be expressed in terms of another variable, say t. That is, we m i y b a p k a f m x = t\$ (t), y = w (t), where the functions t\$ and yj have a common domain. For example, we know that the circle x2 + y2 = a2 is also described by the pair of equations, x = a cost, y = a sint, 0 It I 2%.

i

In such cases the auxiliary variable t is called a parameter and the equations x = t\$(t). y = JJ (t) are called parametric equations. Now, suppose a function is defined in terms of I a parameter. To obtain its derivative, we need only differentiate the relations in x and y separately. The following examples illustrates this method.
dy Example 10 Let us try to find - if x

dx

=

a cos 8 and y

=b

sin 8

(Here the parameter is 8) We differentiate the given equations w.r.t. 8, and get d~ do
,

= b cos 8, and

dx -= do

a sin 0

N o w ~ d x = d x / d e Z Xcot 0 a ZTry to apply this method now.

dy

dy Id0

b cos 0

---

E

E 10) Find ; if i ;
a cos 0, y = a sin 8 at2, y = 2at x = acos3 8, y = bsin3 8 C) d) x = a(8 - sin 8), = a(l - cos 8) a)
,

dy

Elements o f Differential
Calculus

5.5.4 Derivatives of Implicit Functions
It is not always necessary to express y explicitly in terms of x (as in y = f(x)) to find its derivative. We shall now see how to differentiate a function defined implicitly by a relation in x and y (such as, g(x, y) = 0). dy Example 11 Let us find - if x and y are related by dx ax2 + 2hxy + by2 + 2gx + 2fy + c = 0. Differentiating throughout with respect to x, we get

or

-

dy dx

- (ax + hy
=

+ g)
dy for the following implicit functions. dx

,(hx+by+f)
-

See if you can find

E

E 11) Find - if x and y are related as follows:
a) b) c) d) x: + y2 = I y =4ax . x~~~+ x2y2+ xy + 1 = 0 cosx cosy - y2sin-'x + 2x2 tanx

dy dx

=

0

Derivatives of Some Standard Functiens

5.6
1.

SUMMARY
obtained derivatives of the exponential and logarithmic functions, hyperbolic functions and their inverses. We give them in the following table.

In this unit we have

Function
ex
lnx

Derivative
ex 1 X

Function
sinh-' x cosh-' x

Derivative
1

dx'tl
1
, / 3

ax log, X sinh x
I

aXlna
- log, e
X

1

tanh-'x coth-'x sech-'x cosech-'x

1 1-x 2 , I x l < 1 1 I-x
2

cosh x sinh x sech2x -cosech2x -sech x tanh x -cosech x coth x

cosh x tanh x cotb x sech x cosech x

,lx('>l

1 xJm?"<x<l 1

2.
3.

d extended the result - (xr ) dx

= rxr-' to

all x

E

R and x > 0.

illustrated logarithmic differentiation, differentiation of functions involving parameters and differentiation of functions given by implicit relations.

Elements o f Differential calculus

5.7

E2)

e) 22X 1n2 f) 7wSX sinx) In7 (f(x)=2"1n2f(O)=In2 Hence f increases
+

'

times faster at x

=

112 than at x = 0.

-

-

G - 54 sin3 x cos x

1

)

I
X

cos ec h2

(i]

d) - sec h lnx tanh lnx
\

.X

1

e) ex (sinhx + coshx)

b,

- [sec h-' (cos2 ~ ) 1 - ~ ' ~

1

1

3

1

2 c o s x sin x

C) Then f (x) = sin xX(ln sinx + x cotx ) and gf(x) = cosxh
. (sec2x ln cos x - tan2 x) \dY = f (x) + gf(x) dx

Derivatives of Some Standard Functions

~, d) Let f(x) = ( x ~ )g(x) = x("'), x > o If y = xX,lny = xln

E 10)

(x) = x ( ~[xX-' + xXln x (1 + ln x)] ) Answer = f ' (x) + gf(x) = (xX)" h X x(1 + h ) ] + x(=) [\$-I [ + + xx-' 1m (1 + lnx)] d In sin x e) -(sin x)InX= (sin x)InX x cot x + (ln dx x d --(xX)= xX(l+Inx) dx In sin x Answer = (sin x)'"" (I" X Cot x + X + x X ( l+ l n x ) dx dx a) - = - a sin 8, - = a cos 8 d8 de
3 g'

)

b) c) d)

z--dy
-

2a 1 2at t dy 3bsin28cos8 = - - tang - -dx -3acos2 8 sin8 a d~ a sin8 - sin 8 - -dx a(1- cos 8) (1 - cos8)

dy . dy d) - cosx sin y - - sin x cosy - 2y - sin-'x dx dx + 2x2 sec2x = o sinx cosy + 3

YL
+

4x tan x

dy - = dx

Y \r-T
(1-x

- 4x tanx - 2x2 sec2 x

- (cos x sin y + 2y sin-' x))

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->